NOX, NOX Who is There? The Contribution of NADPH Oxidase One to Beta Cell Dysfunction - Taylor-Fishwick, David (Frontiers in Endocrinology, 2013)
Predictions of diabetes prevalence over the next decades warrant the aggressive discovery of new approaches to stop or reverse loss of functional beta cell mass. Beta cells are recognized to have a relatively high sensitivity to reactive oxygen species (ROS) and become dysfunctional under oxidative stress conditions. New discoveries have identified NADPH oxidases in beta cells as contributors to elevated cellular ROS. Reviewed are recent reports that evidence a role for NADPH oxidase-1 (NOX-1) in beta cell dysfunction. NOX-1 is stimulated by inflammatory cytokines that are elevated in diabetes. First, regulation of cytokine-stimulated NOX-1 expression has been linked to inflammatory lipid mediators derived from 12-lipoxyganase activity. For the first time in beta cells these data integrate distinct pathways associated with beta cell dysfunction. Second, regulation of NOX-1 in beta cells involves feed-forward control linked to elevated ROS and Src-kinase activation. This potentially results in unbridled ROS generation and identifies candidate targets for pharmacologic intervention. Third, consideration is provided of new, first-in-class, selective inhibitors of NOX-1. These compounds could have an important role in assessing a disruption of NOX-1/ROS signaling as a new approach to preserve and protect beta cell mass in diabetes.